Chitosan-SnO2 Composite film-based self-powered galvanic cell for detecting ammonia gas at room temperature - Balyan M.; Ahmadipour M.; Ahmad Z.A.; Siregar B. (Springer Science and Business Media Deutschland GmbH, 2025)
Ammonia, recognized as a perilous compound for both environmental and human health, necessitates detection of its varied concentrations in the air for environmental conservation and safety. This study introduces a novel self-powered ammonia gas sensor, operating at room temperature using a chitosan and tin dioxide (SnO?) composite film. Designed based on the galvanic cell principle, the sensor eliminates the need for external power sources, making it ideal for various environmental and industrial applications. Advanced morphological and compositional analyses were conducted through field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray spectroscopy (EDAX), confirming the effective integration of SnO? into the chitosan matrix, enhancing surface oxygen content and porosity. Fourier transform infrared (FTIR) spectroscopy revealed NH? groups in chitosan that interact with ammonia gas. The sensor demonstrated exceptional sensitivity and selectivity towards ammonia, with peak sensitivity reaching 26.13% at 50 ppm, significantly higher than pure chitosan?s 17.14%. The sensor showed a substantial increase in electrical voltage in response to ammonia,effectively distinguishing it from gases such as acetone, ethanol, and toluene. This superior performance is attributed to the interaction between ammonia and NH? groups in chitosan, which promotes the release of trapped electrons. This research marks a significant advancement in gas detection technology, offering an eco-friendly, efficient, and reliable method for ammonia monitoring, essential for environmental protection and industrial safety. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.